ANALISIS POTENSI EKSPOR KOMODITI PERTANIAN UNGGULAN DALAM KERANGKA KEMANDIRIAN PEREKONOMIAN DAERAH DI KABUPATEN BOYOLALI (Pendekatan Location Quotient Analisis) - Ropingi Ropingi; Agustono Agustono; Catur Tunggal BJP (Universitas Sebelas Maret, 2009)
The goal of this research as: (1) to understand of the potensity of export the excellent comodity agriculture from subdistrict in Boyolali. (2) to understand of the contribution of the excellent comodity agriculture in regional economic with the approach of the multiplier value of comodity production. The secunder data is used in this research. The data are taken from BPS Central Java, BAPPEDA Central Java and BPS Boyolali. The method of analysis is used the location quotient for identify the agricultural comodity in subdistrict; and the potensity of export the excellent agriculture comodity to understand of contribution and share from export the excellent agriculture comodity. The result of research: (1) the excellent agriculture comodity from subdistrict in Boyolali is different of the quantity and the kinds, this show the different from carrying capacity of subdistrict in Boyolali (2) the big of the excellent agriculture comodity from subdistrict in Boyolali are different, the value of the excellent agriculture comodity from 60% until 95.14% (3) the contribution the excellent agriculture comodity in subdistrict for regional economic in Boyolali are different. This contribution is shown with the difference of multiplier value of the export the excellent agriculture comodity from subdistrict. The Cepogo subdistrict has the biggest value 4.307, this show the Cepogo subdistrict has the best contribution. Thde sawit subdistrict has the smallest value 1.614, this show the Sawit subdistrict has the lowest contribution. From this research to propose the advanced research with Klassen Tipology approach or another approach as Shift Share, Forward Linkages and Backward Linkages from the excellent of agriculture comodity.